THE EFFECTIVENESS OF LEADERSHIP STYLE, WORKLOAD, AND TURNOVER INTENTION ON HIGH AND LOW EMPLOYEE PERFORMANCE - Angnessianti, Irma Puspita; Musoli, Musoli (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The study aims to (1) test the effect of leadership style and workload on turnover intention and (2) test the effect of leadership style, workload, and turnover intention on employee performance. Method: This study was quantitative using primary data obtained through questionnaires. The sample of the study was all employees of PT. Pos Indonesia KCU (Branch Office) Yogyakarta, totaling 50 respondents. The sampling technique was census sampling on all employees of PT. Pos Indonesia KCU Yogyakarta. Results: It can be concluded that leadership style has a positive and significant effect on turnover intention, workload has a positive and significant effect on turnover intention, turnover intention has a significant and positive effect on employee performance, leadership style has a positive and significant effect on employee performance, and workload has a positive and significant effect on employee performance. Turnover intention can mediate the effect of leadership style and workload on employee performance. Novelty: The equation of this study with previous research lies in several variables measured, namely leadership style, workload, turnover intention, and employee performance, while the difference lies in the subjects and objects studied and based on the literature search that the researchers conducted, no similar research titles have been found that were studied at the Large Post Office in Yogyakarta.